The impact of SARS-CoV-2 infection on vaccinated versus unvaccinated pregnant women: a retrospective cohort study - Noelia Rodríguez-Blanco; Jesús Sánchez-Más; Estela Gimenez Herrero; Paloma Calvo Moreno; Macarena Mateo Gonzalez-Román; José Luis Duro-Torrijos (BMC Pregnancy and Childbirth)
Abstract Background/Objectives Pregnant women were included in the COVID-19 vaccination strategy adopted in Spain in May 2021. We evaluated the obstetric and neonatal symptoms and complications presented by these first pregnant women infected with SARS-CoV-2, vaccinated and unvaccinated. Methods A retrospective observational cohort study of 156 pregnant women with a positive diagnosis of SARS-CoV-2 (infection rate of 4.2%, 156/3719 births), treated at two public hospitals in the Valencian Community (Spain) over two years (2020–2022). Of those pregnant women infected, 28.8% (45) had received at least one dose of the COVID-19 vaccine before infection. The data were obtained from the digital medical record, the Nominal Vaccination Registry (RNV), and symptom data from the Epidemiological Surveillance Application (AVE) of the CV, supervised by the epidemiology units. We analyzed the symptoms of the disease and the main obstetric and neonatal variables depending on whether or not they were vaccinated with mRNA vaccines. Results Most pregnant women were diagnosed in the third trimester of pregnancy (p = 0.003) and reported symptoms associated with the infection (73%), but vaccinated women reported all the symptoms described to a lesser extent, with headache (R1.38, 95%IC 1.15 to 1.66) and vomiting (R 1.38, 95%IC 1.15 to 1.66) statistically significant. All cases of pneumonia occurred in unvaccinated pregnant women who required ventilatory assistance and referral to the Intensive Care Unit. Pregnant women vaccinated against SARS-CoV-2 infection had lower rates of gestational pathology, milder symptoms, and fewer postpartum complications than unvaccinated women, although the small sample size did not allow for a significant difference to be seen. Neonatal outcomes were similar in both groups. Conclusions COVID-19 vaccination in pregnant women with at least one dose is associated with reduced symptoms, less headache and vomiting, and fewer maternal complications, including pneumonia, which did not occur in the vaccinated cohort. Furthermore, the Apgar score at one and five minutes is higher than 7 in children of immunized mothers.Public health strategies should promote access to vaccines during pregnancy as an urgent priority, to minimize the risk of complications from COVID-19.